Band superconductivity in a periodic constricted nanoribbon structure. (October 2021) - Pasek, Wojciech Julian; Degani, Marcos H.; de Andrade, Marcio C.; Maialle, Marcelo Z.
Abstract: Periodic geometrically constricted 2D NbSe2 nanowire is investigated with the Anderson approximation of Bogoliubov-de Gennes (BdG) equations. The superconducting order parameter is related to the single particle DOS around the Fermi level, but the introduction of an inter-cell phase difference changes this relation from average-like (accounting for the miniband-proximity effect) to strictly local. A miniband crossing related "shape resonance" is identified as a function of the periodic constriction. The phase difference leads to modulation or suppression of the superconducting gap which is shown to typically be strictly coupled with the vanishing of the order parameter. However, an exception to the general rule is discussed, where significant Δ ( r ⃗ ) exists with a closed gap as a consequence of the mixing of different transverse symmetries. Possibility to redefine the properties of the system via manipulation of its geometry or the electron concentration is presented. Highlights: Interplay between superlattice quasi-momentum and phase difference. Gapless superconductivity due to transverse parity mixing. System manipulation via chemical potential/electron concentration/current.